Efficiency of Using Innovative Learning Technologies in Enhancing Students’ Cognitive Activity - Artikova Makhim Turaboy kizi (International Journal on Human-Computing Studies, 2022)
The article deals with the issues based on the use of modern technologies in the educational process caused by the integration and information processes taking place in society, the formation of a new education system focused on entering the global educational space. As we know, development is an integral part of any human activity. Moreover, while accumulating experience, improving methods, methods of action, expanding their mental capabilities, a person himself constantly develops.